2019
DOI: 10.1111/ajr.12504
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of prostate‐specific antigen testing by remoteness of residence and socio‐economic status: An Australian population‐based study

Abstract: Objective: Describes the variation in prostate cancer testing by the remoteness of residence and socio-economic status groups in Australia. Design: A national population-based descriptive study using Medicare data extracted by the Department of Health (formerly the Department of Health and Ageing). Setting: Australia.Participants: All men, with a Medicare-reimbursed prostate-specific antigen test conducted in Australia between 2002 and 2017, were included. We focused on "screening and case finding" tests (Medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 17 publications
(34 reference statements)
0
7
0
Order By: Relevance
“…Possible reasons for higher detection rates of cancer in our present TP biopsy study compared to published TRUS biopsy data include a higher number of cores taken and inclusion of other biopsy indications such as abnormal DRE. Additionally, a higher detection rate in our present cohort from a regional city could reflect a geographic or socioeconomic disparity in the incidence of prostate cancer [19,20].…”
Section: Discussionmentioning
confidence: 75%
“…Possible reasons for higher detection rates of cancer in our present TP biopsy study compared to published TRUS biopsy data include a higher number of cores taken and inclusion of other biopsy indications such as abnormal DRE. Additionally, a higher detection rate in our present cohort from a regional city could reflect a geographic or socioeconomic disparity in the incidence of prostate cancer [19,20].…”
Section: Discussionmentioning
confidence: 75%
“…This is not surprising given that PrCa patients from outer regional/remote areas were significantly more likely to reside in areas with lower rates of socio-economic advantage, which may inhibit their access to healthcare, including regular screening check-ups. Another possible factor contributing to the higher rates of advanced disease diagnosed amongst this cohort could be the higher PSA monitoring rates seen in metropolitan regions of Australia and New Zealand compared to rural regions 2 , 7 , 8 . As a rise in PSA is one of the few strategies for early detection of PrCa, limited access to this testing could result in the delay of diagnosis until the disease becomes symptomatic.…”
Section: Discussionmentioning
confidence: 99%
“…These individuals presented with significantly higher prostate-specific antigen (PSA) levels and Gleason scores at diagnosis and also experienced a prominent delay between diagnosis and the commencement of treatment 5 , a factor that could adversely affect outcomes 6 . Furthermore, a nationwide study in 2005 identified 29% lower rates of radical prostatectomy in outer regional and rural areas 3 , and though regular PSA testing is undertaken across Australia, it is more common in capital cities 3 and less in regional and remote areas 7 . A New Zealand study has reported similar discrepancies between rates of PSA screening and men living in rural or urban regions 8 .…”
Section: Introductionmentioning
confidence: 99%
“…This holds true for prostate cancer, with lower uptake of diagnostic and treatment services and worse mortality among rural men 12 . PSA screening and radical prostatectomy rates are lowest among rural men and while survival rates for prostate cancer in Australia are among the highest in the world; in Australia, prostate cancer survival is worst for rural men 11‐13 …”
Section: The Urban‐rural Health Dividementioning
confidence: 99%